Business law - Jane P. Mallor (McGraw-Hill/Irwin, 2010)
Mallor, Barnes, Bowers and Langvardt's: Business Law: The Ethical, Global, and E-Commerce Environment, 14e is appropriate for the two-term business law course. The cases in the 14th edition are excerpted and edited by the authors. The syntax is not altered, therefore retaining the language of the courts. As in recent previous editions, the 14th edition includes a mix of actual AND hypothetical cases